2007
DOI: 10.1055/s-2007-964848
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tissue Doppler in Steroid Users

Abstract: Anabolic steroids cause a variety of side effects, among them a slight concentric left ventricular hypertrophy. The objective of the present study was to clarify if they also induce alterations in left ventricular function. 14 male body builders with substantial intake of anabolic steroids (users) were examined by standard echocardiography and cardiac tissue Doppler imaging. They were compared to 11 steroid-free strength athletes (non-users) and 15 sedentary control subjects. Users showed an increased left ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 35 publications
5
39
1
6
Order By: Relevance
“…Significant differences have not been observed concerning the results of systolic function among groups, which corroborates previous studies of our group in which ventricular function alterations have not been observed in the animals treated with AAS (21) . Similar data have also been found in humans, where increase of cardiac mass was observed by echocardiogram in AAS users and alterations of systolic function have not been noticed (9) . The velocity peak of E wave, velocity peak of A wave, the E/A ratio as well as the isovolumetric relaxing time (IVRT) were used for analysis of the diastolic function.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Significant differences have not been observed concerning the results of systolic function among groups, which corroborates previous studies of our group in which ventricular function alterations have not been observed in the animals treated with AAS (21) . Similar data have also been found in humans, where increase of cardiac mass was observed by echocardiogram in AAS users and alterations of systolic function have not been noticed (9) . The velocity peak of E wave, velocity peak of A wave, the E/A ratio as well as the isovolumetric relaxing time (IVRT) were used for analysis of the diastolic function.…”
Section: Discussionsupporting
confidence: 75%
“…Many investigations have shown the AAS effects on the diastolic function (9)(10)(11) , where decrease in the velocity peak has been observed during the initial phase of diastolic filling and harm in the diastolic function in weight lifters who used AAS compared to the ones who did not use it, being these effects associated with the increase of the interstitial collagen (10,11) . Thus, our results obtained with the association of AAS with aerobic physical training corroborate the data already observed in the literature with resistance training, which promoted adaptations to the cardiovascular system, such as the pathological CH, characterized by increase of interstitial collagen and decrease of diastolic function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that cardiovascular morbidity and mortality have significantly increased in long-term AAS using bodybuilders than nonusers (5) . Furthermore, recent studies have found pathological left ventricular hypertrophy (LVH), diastolic dysfunction [impaired relaxation and decreased compliance of left ventricle (LV)], increased LV mass, left atrial (LA) hypertrophy, subclinical systolic impairment, increased myocardial stiffness and myocardial fibrosis in long-term AAS users (4,(7)(8)(9) . These conditions are independent risk factors for cardiovascular morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%